Custom Hydroxyapatite‐Coated Stem Collar With Extracortical Plate Provides Excellent Long‐Term Results Against Aseptic Loosening in Revision, Including Short‐Segment, Endoprosthetic Tumour Reconstruction - Patrick Qi Wang; Kwok Chuen Wong (Cancer Reports, 2025)
ABSTRACT Background Aseptic loosening from endoprosthetic reconstructions following bone tumour resection is a major issue, especially in the revision/multiple revisions settings. The objective was to present long‐term outcomes of revision limb salvage surgery using a custom hydroxyapatite‐coated stem collar with an extracortical plate at the bone‐implant junction specifically designed to prevent aseptic loosening. Methods Fifteen (15) patients with an initial extremity bone tumour resection and reconstruction who underwent revision surgery utilizing this implant specification between 2004 and 2016 were included. Multiple prior surgeries and short‐segment stem fixation (< 100 mm) were observed in six and nine patients, respectively. Outcomes of interest were rates of aseptic loosening and radiographic evidence of osseointegration along with clinical and functional outcomes. Results At mean 12‐year follow‐up (range 6.5 to 18), no patient had evidence of radiographic or clinical aseptic loosening. The distal femur location (p = 0.044), endoprosthetic reconstruction as index procedure (p = 0.026), mechanical failure as reason for revision (p = 0.0047) and additional fixation to the extracortical plate (p = 0.041) were associated with higher bone ingrowth scores. All but two patients, who had mild pain only, were pain‐free. Joint range of motion (p < 0.0001) and limb‐length discrepancy (p = 0.021) significantly improved. The mean Musculoskeletal Tumor Society score was 26.1 (excellent). Conclusions This study demonstrated excellent results in preventing long‐term aseptic loosening with this custom implant specification, which is useful particularly for revisions/multiple revisions and short‐segment fixation. However, further larger scale and multicentric studies are needed to validate the data to the broader population.